Library Index Management through Library Archives Training at MTs Unggulan Nurul Qur'an Boyolali - Masyath, Khassan; Awaliyah, Avinda Putri; Muslimin, Muhammad Saiful Hidayatul; Azzahra, Fida Uswah (Universitas Pahlawan Tuanku Tambusai, 2025)
In every educational institution, the existence of libraries is very necessary because libraries are the heart of an educational institution, even though in reality the large number of libraries still do not meet the established standards. Employee performance is needed so that the library can run optimally in accordance with applicable regulations. Thus, in this article we will discuss library management and archive management to make it easier for students to find information so that this is very necessary for the sustainability of the library so that it can develop into a more structured one. The method used in this research is descriptive which was studied using a qualitative approach. In qualitative approach research, the data description is in the form of sentences or narratives obtained through qualitative data collection techniques. The findings from the research include making the library function as well as possible, which will provide opportunities for students to learn to read, search for and use information, and research. Apart from that, when the management of library archives related to book codes, the number of books, books lent, books that are still in the period of being coded is implemented well, then when students look for information about their learning material they can easily organize it.